„Politische Analogien“. Demokratisches Denken und Nationalrepräsentation auf der Preußischen General-Synode von 1846 - Schubert, Anselm (Zeitschrift der Savigny-Stiftung für Rechtsgeschichte. Kanonistische Abteilung, 2024)
The Prussian General Synod of 1846 has been understood as the ecclesiastical precursor of the Vereinigte Landtag of 1847. This essay argues that the General Synod was rather convened by the king on the model of the “Vereinigte Ausschüsse “of 1842. To the extent granted to them by the rules of procedure, the synodals adopted democratic ideas and practices within the limits of their “Ständebewußtsein”, widely viewed them critically in the church, and vehemently rejected them in the political context.
CRIS-Team Scopus Importer:2024-08-16
Keywords: 19; Church History; History of Democracy; History of Ideas; Prussia